2020
DOI: 10.1177/1758835920927602
|View full text |Cite
|
Sign up to set email alerts
|

Is the era of sorafenib over? A review of the literature

Abstract: Hepatocellular carcinoma (HCC) is one of the most severe diseases worldwide. For the different stages of HCC, there are different clinical treatment strategies, such as surgical therapy for the early stage, and transarterial chemoembolization (TACE) and selective internal radiation therapy (SIRT) for intermediate-stage disease. Systemic treatment, which uses mainly targeted drugs, is the standard therapy against advanced HCC. Sorafenib is an important first-line therapy for advanced HCC. As a classically effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 156 publications
(201 reference statements)
1
38
0
3
Order By: Relevance
“…In fact, cisplatin, a classic chemotherapy agent, was found to induce ferroptosis through glutathione deletion in certain cancer cell lines [ 165 ]. Sorafenib is a multikinase inhibitor approved for the treatment of advanced cancer (e.g., hepatocellular carcinoma) [ 166 ], and it can be used as an agonist of ferroptosis for its inhibitory effect on system xc- [ 167 ]. More importantly, erastin, a more potent inhibitor of system xc-, has been shown to improve the anticancer activity of traditional chemotherapy drugs (e.g., docetaxel, cisplatin, and temozolomide) in several cancer cells [ 168 170 ].…”
Section: Regulation Of Iron Metabolism For Antitumor Immunitymentioning
confidence: 99%
“…In fact, cisplatin, a classic chemotherapy agent, was found to induce ferroptosis through glutathione deletion in certain cancer cell lines [ 165 ]. Sorafenib is a multikinase inhibitor approved for the treatment of advanced cancer (e.g., hepatocellular carcinoma) [ 166 ], and it can be used as an agonist of ferroptosis for its inhibitory effect on system xc- [ 167 ]. More importantly, erastin, a more potent inhibitor of system xc-, has been shown to improve the anticancer activity of traditional chemotherapy drugs (e.g., docetaxel, cisplatin, and temozolomide) in several cancer cells [ 168 170 ].…”
Section: Regulation Of Iron Metabolism For Antitumor Immunitymentioning
confidence: 99%
“…At an early stage of the disease, HCC can be treated by surgical resection, percutaneous ablation, or liver transplantation. At a later stage, the therapeutic options have been limited during the last decade to Sorafenib (a multikinase inhibitor) [ 7 , 8 ]. Recently, other first-line treatments such as lenvatinib and second-line treatments such as regorafenib and cabozantinib have been proposed for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As an inhibitor targeting multiple tyrosine protein kinases (VEGFR, PDGFR and Raf family kinases), sorafenib acts on numerous targets to inhibit cancer proliferation and tumor angiogenesis, which can effectively lead to a decrease in mortality in HCC patients. 18 , 19 Advanced stage HCC patients can benefit from 400mg twice daily sorafenib therapy. 5 , 6 , 20 To date, however, clinical trials have revealed that only about 30% patients show sensitivity to sorafenib, and HCC usually progresses within 6 months resulting from resistance to sorafenib.…”
Section: Discussionmentioning
confidence: 99%